Clinical characteristics and diagnostic confirmation of Internet addiction in secondary school students in Wuhan, China. Issue 6 (19th February 2014) - Tang, Jun; Zhang, Yao; Li, Yi; Liu, Lianzhong; Liu, Xiujun; Zeng, Hongling; Xiang, Dongfang; Li, Chiang‐shan Ray; Lee, Tony Szu‐Hsien
<x xml:space="preserve">Abstract</x> Aim This study investigated the clinical characteristics of internet addiction using a cross‐sectional survey and psychiatric interview. Methods A structured questionnaire consisted of demographics, Symptom Checklist 90, Self‐Rating Anxiety Scale, Self‐Rating Depression Scale, and Young's Internet Addiction Test (YIAT) was administered to students of two secondary schools in Wuhan, China. Students with a score of 5 or higher on the YIAT were classified as having Internet Addiction Disorder (IAD). Two psychiatrists interviewed students with IAD to confirm the diagnosis and evaluate their clinical characteristics. Results Of a total of 1076 respondents (mean age 15.4 ± 1.7 years; 54.1% boys), 12.6% (n = 136) met the YIAT criteria for IAD. Clinical interviews ascertained the Internet addiction of 136 pupils and also identified 20 students (14.7% of IAD group) with comorbid psychiatric disorders. Results from multinomial logistic regression indicated that being male, in grade 7–9, poor relationship between parents and higher self‐reported depression scores were significantly associated with the diagnosis of IAD. Conclusion These results advance our understanding of the clinical characteristics of Internet addiction in Chinese secondary school students and may help clinicians, teachers, and other stakeholders better manage this increasingly serious mental condition.